2000
DOI: 10.3354/meps195261
|View full text |Cite
|
Sign up to set email alerts
|

Variability in mercury concentrations of great skuas Catharacta skua:the influence of colony, diet and trophic status inferred from stable isotope signatures

Abstract: A range of parameters thought to contribute to intra-specific variation in mercury levels were investigated using the feathers and blood of adult great skuas Catharacta skua from 2 northeast Atlantic colonies as sampling units. Different feather types and blood were taken to represent intake over different temporal scales Mercury concentrations and stable isotope signatures of these tissues were determined. General linear models demonstrated that trophic status, as indicated by FI5N, had an influence on tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 22 publications
6
79
0
3
Order By: Relevance
“…Within this framework, monitoring animal exposure to pollutants derived from local foodwebs is crucial to evaluate the actual impact of such pollution on wildlife communities and on the ecosystem as a whole. In this regard and as many previous studies had found, THg, Se and Pb levels in fledgling feathers varied geographically confirming that baseline levels of these elements at different colony sites easily influence tissue burdens, especially at high trophic levels (Bearhop et al, 2000;Gochfeld, 1997;Ramos et al, 2009a;Ricca et al, 2008;Thompson et al, 1992). However, more importantly, this study concluded that exploited feeding habitats may affect pollutant burden of a given individual, in a greater manner than its own trophic position does.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Within this framework, monitoring animal exposure to pollutants derived from local foodwebs is crucial to evaluate the actual impact of such pollution on wildlife communities and on the ecosystem as a whole. In this regard and as many previous studies had found, THg, Se and Pb levels in fledgling feathers varied geographically confirming that baseline levels of these elements at different colony sites easily influence tissue burdens, especially at high trophic levels (Bearhop et al, 2000;Gochfeld, 1997;Ramos et al, 2009a;Ricca et al, 2008;Thompson et al, 1992). However, more importantly, this study concluded that exploited feeding habitats may affect pollutant burden of a given individual, in a greater manner than its own trophic position does.…”
Section: Discussionsupporting
confidence: 86%
“…To our interest, chick feathers grow slowly and constantly throughout the chick-rearing period (personal observation) and they are formed from the dietary inputs received at the colony site (Becker et al, 1994). Although feather elements are routed from blood and liver before being excreted into growing feathers, with the sampling of chick feathers we avoided bioaccumulation biases and severe biogeochemical routing from other internal organs (such as muscle or fat) which might cause great impact in biogeochemical profiles due to potential seasonal movements and dietary shifts of the adult individuals (Bearhop et al, 2000;Sanpera et al, 2007). Chicks and fledglings diet of these colonies of Yellow-legged gull is described in detail in Ramos et al (2009b) through conventional analysis of regurgitates.…”
Section: Study Area and Sampling Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…First, it focuses on a community of tropical seabirds for which, except for albatrosses (Finkelstein et al 2006, Awkerman et al 2007), almost nothing is known about their δ 13 C and δ 15 N values. Second, while isotopic signature of several tissues (liver, muscle, bone) to infer seabird diet at different temporal scales was previously investigated (Hobson 1993), the present work is the first using δ 13 C and δ 15 N values of adult blood and feathers (Bearhop et al 2000) to study trophic structure of a community during the breeding and non-breeding periods, respectively. Finally, we compared the trophic position (δ 15 N) of seabirds with that of other marine predators, an issue rarely investigated in the past (Hobson & Welch 1992).…”
Section: Discussionmentioning
confidence: 99%